2011
DOI: 10.1016/j.stem.2011.01.017
|View full text |Cite
|
Sign up to set email alerts
|

Targeting SOX17 in Human Embryonic Stem Cells Creates Unique Strategies for Isolating and Analyzing Developing Endoderm

Abstract: Human embryonic stem cells (hESCs) can provide insights into development of inaccessible human tissues such as embryonic endoderm. Progress in this area has been hindered by a lack of methods for isolating endodermal cells and tracing fates of their differentiated progeny. By using homologous recombination in human ESCs, we inserted an enhanced green fluorescent protein (eGFP) transgene into the SOX17 locus, a postulated marker of human endoderm. FACS purification and gene expression profiling confirmed that S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
97
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(103 citation statements)
references
References 42 publications
5
97
1
Order By: Relevance
“…Because activin A-induced differentiation does not generate homogenous cell population (Supplementary information, Figure S1B), we used CD184 (also named CXCR4), a well-known definitive endoderm marker [4,[19][20][21], to sort the cell population and confirmed successful endoderm differentiation by RT-qPCR analysis (Supplementary information, Figure S1C). In addition to CD184, another report [20] used both CD184 and CD117 (also named c-KIT) to mark the definitive endoderm cell population.…”
Section: Resultsmentioning
confidence: 99%
“…Because activin A-induced differentiation does not generate homogenous cell population (Supplementary information, Figure S1B), we used CD184 (also named CXCR4), a well-known definitive endoderm marker [4,[19][20][21], to sort the cell population and confirmed successful endoderm differentiation by RT-qPCR analysis (Supplementary information, Figure S1C). In addition to CD184, another report [20] used both CD184 and CD117 (also named c-KIT) to mark the definitive endoderm cell population.…”
Section: Resultsmentioning
confidence: 99%
“…Wang et al established a Sox17/GFP knock-in human ES cell line, and carried out gene expression analysis of Sox17/GFP+ cells that were differentiated based on the procedure established by the D'Amour group. The results of their gene expression analysis, in vitro differentiation, and transplantationbased assays showed that CD49e+CD141+CD238+ cells are primitive gut tube endoderm cells [26]. Human ES cell lines were established, with a Sox17/GFP or Pdx1/GFP transgene introduced via BAC vectors.…”
Section: Gene Profiling Of Human Es Cell-derived Cellsmentioning
confidence: 99%
“…G protein-coupled receptor 50 (GPR50) and tumorassociated calcium signal transducer 2 (TROP2) were identified as cell surface proteins that were highly enriched in pancreatic progenitor cells [27]. The identification of cell surface marker genes enabled the isolation of DE [11,28], primitive gut tube endoderm [26], and pancreatic progenitor cells [27], without genetic manipulation of ES cells. This method represents a powerful tool for future characterization of similar cell populations.…”
Section: Gene Profiling Of Human Es Cell-derived Cellsmentioning
confidence: 99%
“…Expression data were obtained from the Gene Expression Omnibus (GEO) database. 42 The used data sets 19,[43][44][45][46][47][48][49][50][51][52][53][54][55] are summarized in Table 1. Primary data analysis was performed with Expression Console (Affymetrix) applying the Microarray Suite 5 algorithm.…”
Section: Cells and Cell Culture Pbmc DC Eft Cell Lines A673mentioning
confidence: 99%